ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS MAHASISWA PADA MATERI GEOMETRI SUDUT - Wantika, Restu Ria (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2017)
Purpose done research to know how mathematical communication ability of student either in writing or orally.The type of this research is descriptive research with qualitative approach. The subjects of the research are S-1 students of Mathematics Education Department of UNIPA Surabaya who are taking angle geometry courses that have good mathematical communication ability, good enough and less good that has been predicted by mathematics teacher in that class. Methods of data collection used were observations during learning, tests and in-depth interviews. Research instruments are diagnostic tests and interview guidelines. Data analysis in this research is descriptive qualitative analysis. The data analyzed are observational data during the learning, test results and in-depth interviews that are used to describe students' mathematical communication abilities in writing and orally. The results obtained from this study among others. The result of the analysis of students who have the ability of mathematical communication as a whole found that 28.65% are at level 4, where students are able to use math language (term, symbol, sign, and or representation) which is very effective, accurate and comprehensive. Furthermore, 21.87% of students are at level 3, where students are able to use math language (terms, symbols, signs, and or representations) that are less effective but accurate. So also students who have the ability of mathematical communication at level 2 is 19.78%. Where at level 2 students are able to use math language (terms, symbols, signs, and or representations) that are less effective. Furthermore 25% of students are at level 1, where students in using mathematics language (term, symbol, sign, and or representation) are inaccurate and ineffective. At level 0 where the student does not give answer as much as 4.67%. Keywords: analysis of mathematical communication skills, angular geometry